Training Effectiveness at PT XYZ Using Kirkpatrick Model and Return on Investment of Training (ROI-Training) - Jonny, Jonny (Binus Business Review, 2016)
The goal of the research was to evaluate the effectiveness of Kirkpatrick model and Return on Investment of Training at PT XYZ. Observation was applied to this research. The result has shown several facts such as traineeâs feedback score was 4,62 above 4,10 as required by the company in terms of reaction, the average final exam score was 3,66 above 3,00 as required by the company in terms of learning, the traineesâ superiorsâ feedback score was 3,53 above 3,00 as required by the company and Return on Investment of Training (ROI-Training) was 58,88% above 15% as required by the company. With these results, the company can conclude that the program is effective in nurturing its supervisory leaders.